Management of Infections with Rapidly Growing Mycobacteria after Unexpected Complications of Skin and Subcutaneous Surgical Procedures - Jong Min Lim; Jong Hwan Kim; Ho Jik Yang (Archives of Plastic Surgery, 2012)
BackgroundInfection caused by rapidly growing mycobacteria (RGM) is not uncommon, and the prevalence of RGM infection has been increasing. Clinical diagnosis is difficult because there are no characteristic clinical features. There is also no standard antibiotic regimen for treating RGM infection. A small series of patients with RGM infections was studied to examine their treatments and outcomes.MethodsA total of 5 patients who had developed postoperative infections from January 2009 to December 2010 were retrospectively reviewed. Patients were initially screened using a mycobacteria rapid screening test (polymerase chain reaction [PCR]-reverse blot hybridization assay). To confirm mycobacterial infection, specimens were cultured for nontuberculous mycobacteria and analyzed by 16 S ribosomal RNA and rpoB gene PCR.ResultsThe patients were treated with intravenous antibiotics during hospitalization, and oral antibiotics were administered after discharge. The mean duration of follow-up was 9 months, and all patients were completely cured of infection with a regimen of a combination of antibiotics plus surgical treatment. Although none of the patients developed recurrence, there were complications at the site of infection, including hypertrophic scarring, pigmentation, and disfigurement.ConclusionsCombination antibiotic therapy plus drainage of surgical abscesses appeared to be effective for the RGM infections seen in our patients. Although neither the exact dosage nor a standardized regimen has been firmly established, we propose that our treatment can provide an option for the management of rapidly growing mycobacterial infection.